2010
DOI: 10.1109/tie.2009.2037652
|View full text |Cite
|
Sign up to set email alerts
|

Energy Harvesting From Vibration With Alternate Scavenging Circuitry and Tapered Cantilever Beam

Abstract: Piezoelectric transducers are increasingly being used to harvest energy from environmental vibrations in order to either power remote sensors or charge batteries that power the sensors. In this paper, a new voltage compensation scheme for high-voltage-based (> 100 V) energy harvesting is introduced, and its fundamental concepts, as well as the operation details, are elaborated. This scheme, when applied to the voltage inversion method [synchronized switch harvesting on inductor (SSHI)], provides an increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 20 publications
(45 reference statements)
0
30
0
Order By: Relevance
“…This SSHI technique can be implemented with many configurations, which are called parallel SSHI, series SSHI and Synchronous Electric Charge Extraction (SECE). Recently some other groups [4][5] have proposed innovative schemes leading to better performance. Each of these configurations is defined by the relative position of the pair switch-inductor.…”
Section: Fig 1 Generic Energy Harvester System Schematicmentioning
confidence: 99%
“…This SSHI technique can be implemented with many configurations, which are called parallel SSHI, series SSHI and Synchronous Electric Charge Extraction (SECE). Recently some other groups [4][5] have proposed innovative schemes leading to better performance. Each of these configurations is defined by the relative position of the pair switch-inductor.…”
Section: Fig 1 Generic Energy Harvester System Schematicmentioning
confidence: 99%
“…Mehraeen et al 13 have demonstrated that tapered cantilever beams are more effective in generating uniform strain profile over rectangular and trapezoidal beams and resulting in increased harvested power. The harvested energy from the piezoelectric energy harvester is maximized by varying the thickness of the beam along its length which produces more uniform strain distribution along piezoelectric element length.…”
Section: Introductionmentioning
confidence: 99%
“…It has a competent control circuit to adjust the output voltage generated from rectifier. In PZT, the direct connection to the load is not recommended to increase the power harvested (Mehraeen et al, 2010). Therefore, they suggested an efficient stand-alone of energy harvesting circuit consist of a PZT cantilever beam, rectifier, voltage inversion circuitry and power converter.…”
Section: Introductionmentioning
confidence: 99%